1984
DOI: 10.1128/iai.46.3.668-672.1984
|View full text |Cite
|
Sign up to set email alerts
|

A role for rheumatoid factor enhancement of Plasmodium falciparum schizont inhibition in vitro

Abstract: Studies were undertaken to determine whether rheumatoid factor (RF) was present in immune human and Aotus trivirgatus monkey sera which inhibited Plasmodium falciparum schizonts in vitro and to determine whether RF could be responsible for or contribute to merozoite agglutination in the parasite inhibition test. Additional studies were conducted to determine the effect of exogenous RF on schizont inhibition when used alone or in conjunction with immune or normal sera. RF was not detected in any of the 11 immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…There was a positive and significant correlation between antimalarial antibody titre and the serum level of RF as well as 'protein coefficient'. Some authors [49] have reported that RF is produced during active or chronic malarial infection and that it might contribute non-specifically to the enhanced clearance of plasmodia. It is also well known that chronic exposure to malarial parasites can lead to polyclonal stimulation of immunoglobulin cells and thus to an increased frequency of AAb [50].…”
Section: Discussionmentioning
confidence: 99%
“…There was a positive and significant correlation between antimalarial antibody titre and the serum level of RF as well as 'protein coefficient'. Some authors [49] have reported that RF is produced during active or chronic malarial infection and that it might contribute non-specifically to the enhanced clearance of plasmodia. It is also well known that chronic exposure to malarial parasites can lead to polyclonal stimulation of immunoglobulin cells and thus to an increased frequency of AAb [50].…”
Section: Discussionmentioning
confidence: 99%
“…The PIT (Green et al 1981;Green & Packer, 1984) was employed to measure two kinds of inhibition mediated by the MoAbs: (1) their ability to prevent an increase in parasitaemia (growth inhibition, GI) and (2) their ability to prevent the dispersal of merozoites from mature schizonts (schizont inhibition, SI). Parasitized erythrocytes were synchronized to ring stages using 5 % sorbitol (Lambros & Vanderberg, 1979).…”
Section: Parasite Inhibition Test (Pit)mentioning
confidence: 99%
“…A protective role for IgM-RF in immunity to malaria was first demonstrated by Green & Packer (1984), who showed that human RF could enhance the agglutination of P. falciparum merozoites coated with immune human or Aotus monkey IgG by crosslinking the Fc fragments of the parasite-specific antibodies. Removal of the IgM-RF from sera by adsorption against rabbit IgG-coated sheep red blood cells abolished the enhancing effect of the sera.…”
Section: Introductionmentioning
confidence: 99%
“… Might induction of NeRFa be a future promising method not only against malaria as suggested in Ref. ( 33 ), but also against life-threatening viruses like Ebola ( 34 )? …”
mentioning
confidence: 99%